Australian Dog Owners’ Acceptance of Insect-Based Pet Food - Anna Triggs; Ishka Bless; Lukas Danner; Maria Saarela; Kerry Wilkinson (Insects)
Insect-based dog food is increasingly becoming available in pet food markets, potentially offering environmental and nutritional benefits, depending on insect species and how they are reared, processed, and utilized. However, there is limited understanding of dog owners’ attitudes towards the use of insects as protein alternatives for dogs. An online survey was conducted to explore Australian dog owners’ (n = 201) attitudes towards insect-based pet food, segmenting participants according to their food neophobia, previous insect consumption, and dog-human relationship. Participants’ dog food purchases were highly influenced by perceived health/nutrition, palatability, and product quality, with these factors being of most importance to ‘dog people’ (i.e., participants with closer relationships with their dogs). Participants were reasonably accepting of insect-based pet food made from mealworms and crickets and slightly accepting of products made from black soldier fly larvae. In contrast, participants’ responses to plant-based pet foods were neutral. Food neophiles, and to a lesser extent, insect-eating consumers (i.e., those who had previously eaten insects), were found to be more willing to feed their dogs insects in comparison to non-neophiles and non-insect-eating consumers. Overall, Australian dog owners appear to be supportive of feeding their dogs diets supplemented with insect protein. Insights from this study will help inform the development and marketing of insect-based pet foods.